2005
DOI: 10.1111/j.1445-2197.2005.03519.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of deep atypical lipomas (well‐differentiated lipoma‐like liposarcomas) of the extremities

Abstract: We believe the term atypical lipoma is appropriate for these tumours, as they appear not to have any metastatic potential, merely a propensity to recur locally. The chance of dedifferentiation is small and radiotherapy may play a role in its causation. We suggest that a simple marginal resection (shelling-out) is adequate treatment for these lesions. Radiotherapy should not be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 11 publications
5
62
0
2
Order By: Relevance
“…In past literatures, these recurrences have been reported to be between 40 and 67%. 3,5,6,9,13,18 In this current study, 2 out of 3 cases (67%) that underwent reoperation after recurrence demonstrated multiple recurrences, both of which were operated with marginal resection. Thus, preference for reoperation for recurrence is given to wide resection; however, because reoperation often reveals strong adhesion and makes contact with important nerves and vessels, the demerits of wide resection should also be considered.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In past literatures, these recurrences have been reported to be between 40 and 67%. 3,5,6,9,13,18 In this current study, 2 out of 3 cases (67%) that underwent reoperation after recurrence demonstrated multiple recurrences, both of which were operated with marginal resection. Thus, preference for reoperation for recurrence is given to wide resection; however, because reoperation often reveals strong adhesion and makes contact with important nerves and vessels, the demerits of wide resection should also be considered.…”
Section: Discussionmentioning
confidence: 90%
“…Those who recommend marginal resections have suggested the limitations of their research in terms of their short follow-up periods, and also note that recurrence rates can increase as the follow-up period is increased in duration. 8,9 Rozental et al 6 and Macrogenesis et al 18 both report the necessity of at least 5 or 6 years follow-up, and we set the general median-term follow-up of 5 or more years as a cutoff point of our observation period. Among studies describing the clinical outcome of ALT in the extremities, our study has the longest minimum follow-up period.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Postoperative radiotherapy has been shown to be efficient for the myxoid type of liposarcoma [14]. However, a study recommends avoiding radiotherapy since the radiotherapy may induce de-differentiation although the chance is rare in well-differentiated liposarcoma [15]. Chemotherapeutic intervention has been performed for liposarcoma; however there is no established chemotherapy for liposarcoma [16].…”
Section: Discussionmentioning
confidence: 99%
“…An example is well differentiated liposarcoma (often called atypical lipomatous tumor) in the extremities and trunk wall, for which a marginal excision is the preferred primary approach. 24 The risk of recurrence is in the 30% range, and a wider resection can be planned reasonably at the time of recurrence. 25 Furthermore, because the risks of dedifferentiation and systemic spread are negligible in these tumors, function preservation is a principal goal.…”
Section: Personalizing Surgerymentioning
confidence: 99%